Compositional and morphological analysis of FeW films modified by sputtering and heating. (August 2017) - Ström, Petter; Primetzhofer, Daniel; Schwarz-Selinger, Thomas; Sugiyama, Kazuyoshi
Highlights: Tungsten enrichment in FeW films due to preferential sputtering studied. Ion fluence dependence of tungsten depth profile determined. Atomic force microscopy shows protrusions after erosion of films. Interdiffusion of iron and silicon changes film composition around 500 K. Abstract: Surface compositional changes of iron-tungsten films by deuterium (D) ion bombardment were studied by means of medium energy ion scattering, elastic recoil detection analysis and Rutherford backscattering spectrometry. The energy of the bombarding ions was 200 eV/D and the fluence was varied from 10 21 D/m 2 to 10 24 D/m 2 . A significant increase of the tungsten concentration within the 20 nm closest to the sample surface, caused by preferential sputtering of iron, was seen for the films exposed 10 23 D/m 2 or more. In the sample exposed to the highest fluence, 10 24 D/m 2, the concentration of tungsten was increased from an initial 1.7 at. % up to approximately 24 at. % averaged over the 5 nm closest to the surface. The analysis was complicated by the presence of oxygen on the sample surfaces. In order to study the thermal stability of the tungsten enriched layer, the sample initially exposed to 10 23 D/m 2 at room temperature was heated to 400 °C in the measurement chamber for medium energy ion scattering and several spectra were recorded at intermediate temperatures. The obtained data showed that the layer was relatively stable below 200 °C whereas a drastic change in the film composition occurred between 200 °C and 250 °C due to interdiffusion of iron and silicon, the latter of which was the substrate material. The surface morphologies of the films were probed with atomic force microscopy showing that protrusions of 10–100 nm width appeared after deuterium bombardment at fluences higher than 10 22 D/m 2 .